An Assessment of the Antibacterial Activities, Phytochemistry and Toxicities of Nigella damascena L. Seed Extracts - Kim, Jinwoo; Rusford, Enoch John; Tiwana, Gagan; Alcorn, Sean Robert; Cock, Ian Edwin; Cheesman, Matthew James (Pharmacognosy Communications)
Background: Nigella damascena L. (ND) seeds have been incorporated into traditional plant-based medicinal systems for millennia. However, there are conflicting reports on the antibacterial activities of the seed extracts, although phytochemicals known to possess antibacterial activity have been found in the seeds of this species. The toxicities of the extracts have not been studied previously. Aim: This work assesses the ability for aqueous and methanolic ND seed extracts to inhibit the growth of a panel of skin pathogens on agar and in broth, including methicillin-resistant Staphylococcus aureus (MRSA). Qualitative determinations of the phytochemical constituents of the extracts were performed, as well as their toxicity levels. Materials and Methods: Bacterial growth inhibition was evaluated using agar disc diffusion and liquid broth microdilution assays, whilst Artemia nauplii bioassays were used to screen toxicities. Qualitative phytochemical assays were conducted to assess the relative abundance of several important phytochemical compound classes. Results: No inhibition was observed on agar for either the aqueous or methanolic extracts against S. aureus, MRSA, S. epidermidis or S. pyogenes. This was concordant with the liquid microdilution broth assays, with the exception of the methanolic ND extract against S. pyogenes, which produced a minimum inhibitory concentration value of 481 μg/mL. Phenols, saponins, tannins and alkaloid were present in both extract types, while flavonoids could be detected in the methanolic extract only. Both extracts were deemed to be nontoxic in the Artemia nauplii assay. Conclusion: The ND methanolic extract possessed activity against S. pyogenes in liquid broth, but not on agar. The presence of flavonoids in this extract may be responsible for this activity. The extracts were inactive against S. aureus, MRSA and S. epidermidis in agar and broth assays, and were also nontoxic as adjudged by the Artemia nauplii brine shrimp assays.
Keywords: Nigella damascena; Natural products; Antibiotic resistance; MRSA; Toxicities; Bacterial growth.